Re-membering and Dismembering: Memory and the (Re)Creation of Identities in Videogames - Mukherjee, Souvik (Sessões do Imaginário, 2017)
The Prince of Persia in Prince of Persia: The Sands of Time (Ubisoft 2003) is ever reluctant to accept an ignominious end to his story, whether after a fall from atop a tower or after being killed by the sand demons. Every time he fails, the Prince exclaims ‘no no, that is not how it happened at all’. Like the videogame player controlling his avatar, the Prince wants the game sequence to be reloaded and replayed; only he appeals to an entity that the player often does not notice – memory. The Prince justifies the reload because he does not remember the events as they happen and he hankers for a return to a ‘true’ memory. There is an implicit problem here, however. We cannot ask the Prince what he remembers and during the game the player ends up remembering the ‘false’ memories, albeit often unconsciously. To progress further in the game, the player needs to have learned from his mistakes or, in other words, to have remembered the previous iterations of gameplay. According to the Prince’s memory, these failed instances of gameplay never happened; yet they happened in the gameplay and are remembered by players.  Often, many players share the same experience and this exists as a shared memory. Players might also be drawing on collectively recorded memories – the written step by step guidelines in a walkthrough and the comments left by players on various gaming forums or wikis.  What the player remembers is also often influential in determining the in-game identity of the player. Videogames themselves, such as Assassin’s Creed (Ubisoft 2008) and STALKER: Shadow of Chernobyl (GSC Gameworld 2007) have started self-reflexively exploring memory in their plots. Therefore, it will be useful to move the study of memory in videogames out of its relative obscurity and explore its multi-layered complexity.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé